Obtaining patient torso geometry for the design of scoliosis braces. A study of the accuracy and repeatability of handheld 3D scanners. Issue 4 (24th August 2022) - Sanz-Pena, Inigo; Arachchi, Shanika; Curtis-Woodcock, Niven; Silva, Pujitha; McGregor, Alison H.; Newell, Nicolas
Abstract : Objective: Obtaining patient geometry is crucial in scoliosis brace design for patients with adolescent idiopathic scoliosis. Advances in 3D scanning technologies provide the opportunity to obtain patient geometries quickly with fewer resources during the design process compared with the plaster-cast method. This study assesses the accuracy and repeatability of such technologies for this application. Methods: The accuracy and repeatability of three different handheld scanners and phone-photogrammetry was assessed using different mesh generation software. Twenty-four scans of a single subject's torso were analyzed for accuracy and repeatability based on anatomical landmark distances and surface deviation maps. Results: Mark II and Structure ST01 scanners showed maximum mean surface deviations of 1.74 ± 3.63 mm and 1.64 ± 3.06 mm, respectively. Deviations were lower for the Peel 1 scanner (maximum of −0.35 ± 2.8 mm) but higher with the use of phone-photogrammetry (maximum of −5.1 ± 4.8 mm). The mean absolute errors of anatomical landmark distance measurements from torso meshes obtained with the Peel 1, Mark II, and ST01 scanners were all within 9.3 mm (3.6%), whereas phone-photogrammetry errors were as high as 18 mm (7%). Conclusions: Low-cost Mark II and ST01 scanners are recommended for obtaining torso geometries because of their accuracy and repeatability. Subject's breathing/movement affects the resultant geometry around the abdominal and anterolateral regions.